Peran mediasi behavior finance dalam preferensi berinvestasi Milenial dan Gen Z - Widyaningsih, Dewi; Susilowati, Heni; Hargyatni, Titin (Nur Science Institute, 2024)
This study aims to examine the relationships between financial experience, financial socialization, return, risk, and fintech on investment intention, with behavioral finance as a mediating variable, among Millennials and Gen Z in Semarang Regency. The research adopts a quantitative causal approach, utilizing a survey method with data collected through questionnaires from 100 respondents. The findings reveal that financial experience, risk, and fintech significantly influence behavioral finance, while financial socialization and return do not. Furthermore, financial experience, return, risk, fintech, and behavioral finance have significant effects on investment intention, whereas financial socialization does not. Path analysis indicates that behavioral finance mediates the effects of financial experience, risk, and fintech on investment intention. However, it does not mediate the relationships between financial socialization or return and investment intention. These results highlight the importance of financial experience, risk perception, and fintech adoption in shaping investment intentions and the mediating role of behavioral finance in these relationships.